Epibiotic mites associated with the invasive Chinese mitten crab Eriocheir sinensis - new records of Halacaridae from Poland - Monika Normant; Andrzej Zawal; Tapas Chatterjee; Dagmara Wójcik (Oceanologia)
Seven epibiotic halacarid mites (Caspihalacarus hyrcanus, two species of Copidognathus, Halacarellus petiti, Porohalacarus alpinus,Soldanellonyx monardi and S. chappuisi), two oribatid mites (Hydrozetes lacustris and Trhypochthoniellus longisetus) andone water mite (Piona pusilla) were found on the setae-covered claws of eighteen Chinese mitten crabs (Eriocheir sinensis) collected from fresh andbrackish waters in Poland and Germany. The most abundant of the 111 mite individuals recorded was one of the Copidognathus species (N = 52); this was followed by H. petiti (N = 38) and C. hyrcanus (N = 13). This is the first record of H. petiti and of the genus Copidognathus from Polish waters. The possibility of migrating over long distances assisted by catadromous mitten crabs enhances mite dispersal, as well as their introduction to new environments.